Pengaruh Kemampuan Masyarakat Terhadap Program Reboisasi dan Persepsi Terhadap Fungsi Hutan Dengan Perilaku Dominant Social Paradigm - Rosadi Rofik (IJEEM - Indonesian Journal of Environmental Education and Management, 2016)
This study is a path analysis study on the ability of the community on reforestation and their perceptions of the functions of the forest who live around the forest Protected Mangunan Village, District Dlingo, Bantul, Yogyakarta Special Province with the application of management concepts and using a scale behavior of dominant social attitudes paradgm. The study looked at the behavior of the people who live around the village protected forest Mangunan to conclude anti-environmental stance or pro-environmental, behavioral attitudes scala dominant social paradigm in identifying this as a tool for the prevention of deforestation. Results from the first attitude measurement scale, then validated to calculate the scale of subsequent attitude to obtain reliable results. The results showed: first; there is a negative influence between the ability of society to reforestation programs with the behavior of dominant social paradigm, the second; there is a negative influence between the public perception of forest functions with the behavior of dominant social paradigm, the third; there are positive influence between the ability of society to reforestation programs with the public perception of forest functions.